Renoprotective effect of N-acetylcystein and vitamin E in bisphenol A-induced rat nephrotoxicity; Modulators of Nrf2/ NF-κB and ROS signaling pathway. - Abdelrazik, Eman; Hassan, Hend Mohammed; Abdallah, Zienab; Magdy, Alshimaa; Farrag, Eman A (Acta Biomedica Atenei Parmensis, 2022)
Background and aim of the work: Bisphenol A (BPA) is a chemical product that is widely used as a plastic precursor. It acts directly on the kidney mitochondria, causing renal dysfunction. N-acetylcysteine is effective in protecting the kidneys from chemical-induced damage. Vitamin E is an antioxidant that protects cells from the damaging effects of free radicals. The aim of this study is to further evaluate and compare NAC and vitamin E to oppose the nephrotoxicity caused by BPA. Research design and Methods: Forty-two adult male rats were divided into 7 groups:  control, BPA, NAC, vitamin E, BPA plus NAC, BPA plus vitamin E, and combined BPA, NAC and vitamin E. BPA, NAC, vitamin E were given orally at doses of 50 mg/kg, 200 mg/kg, and 1000 mg/kg respectively, for 5 weeks. Results: NAC and vitamin E groups showed improved kidney function tests and alleviated BPA-induced oxidative stress; increased GSH and decreased MDA, NO and iNOS levels. NAC and vitamin E significantly attenuated inflammation; decreased NF-κB and increased IL-4, and Nrf2, in addition there was alleviation of renal histopathology. To some extent, vitamin E administration showed significant improvement. Moreover, combined NAC and vitamin E treatment showed more significance than either NAC or vitamin E separate groups. Conclusions: This study determined the substantial protective effects of NAC and/or vitamin E in BPA-induced nephrotoxicity through modulation of Nrf2 with subsequent improvement of oxidative stress and inflammation. The alleviation was more significant in combined NAC and vitamin E treatment mainly through their synergistic effect on Nrf2.